Spatial Learning Is Impaired in Male Pubertal Rats Following Neonatal Daily but Not Randomly Spaced Maternal Deprivation - Stoneham, Emily T.; McHail, Daniel G.; Samipour-Biel, Sabina; Liehr, Nicole; Lee, Christina M.; Evans, Jean C.; Boggs, Katelyn; Dumas, Theodore C. (Frontiers in Cell and Developmental Biology, 2021)
Severe early life stress has long been associated with neuropsychological disorders in adulthood, including depression, schizophrenia, post-traumatic stress disorder, and memory dysfunction. To some extent, all of these conditions involve dysregulation of the hypothalamic-pituitary-adrenal axis and reduced negative feedback inhibition of cortisol release in adulthood. However, the time course for mental health and hormonal outcomes across life stages and the attributes of early life stress that direct the behavioral and biological alterations is not fully understood. We designed our studies to compare outcomes of the two most common maternal deprivation schedules on cognitive ability prior to adulthood. We exposed rat pups to daily or randomly spaced maternal separation bouts within the first three weeks of life and examined cognitive performance, neurotrophic signaling, and stress and immune system markers during puberty. We found that the daily separation schedule impaired spatial learning while the randomly spaced schedule did not alter maze performance relative to normally reared control animals. Animals that underwent daily separation showed a tendency for reduced body weight compared to the randomly spaced condition, but there were no differences in adrenal weight. Thymus weight normalized by body weight was increased following daily separation compared to random separation and control conditions. Plasma corticosterone levels measured after behavior testing did not differ amongst experimental groups and there was no impact of TrKB receptor inhibition. Combined, the results show that different early life stress schedules produce different behavioral and biological outcomes when measured at puberty. Combined with prior findings from more mature animals, the results presented here suggest that daily neonatal stress produces varied alterations in spatial cognition at different life stages with a transient learning deficit at puberty preceding a more persistent and a progressive memory impairment through adulthood and into aging.